Comparing radiation toxicities across species: An examination of radiation effects in Mus musculus and Peromyscus leucopus. (June 2013) - Liu, William; Haley, Benjamin; Kwasny, Mary J.; Li, Jian Jian; Grdina, David J.; Paunesku, Tatjana; Woloschak, Gayle E.
Abstract Purpose: Life shortening and pathological complications in similarly irradiated cohorts of the laboratory mouse Mus musculus and the white-footed mouse Peromyscus leucopus were recorded in the course of the Janus studies conducted at Argonne National Laboratory from 1970–1992. This study examines how lifespan, tumor and non-tumor disease incidence, and tumor multiplicity are differentially affected by gamma-rays and neutron radiation exposure in two different animal species. Materials and methods: Survival analyses examined differences in lifespan across species, while decision tree analyses examined statistically significant associations between lifespan, radiation exposure, and specific diseases. Logistic regression models were generated to examine the likelihood of disease incidence in these two species following gamma-ray or neutron radiation exposure. Results: Life shortening in response to radiation was more significant in Peromyscus leucopus than in Mus musculus, irrespective of radiation quality. Many types of tumor and non-tumor diseases were found to be consistently species specific. Tumor multiplicity was observed in both species in response to radiation, although more pronounced in Mus musculus. Conclusion: The response to radiation was highly species specific, highlighting the difficulty in extrapolating conclusions from one species to another, irrespective of their phenotypic similarities and ecologic niches.